Genomics-enabled learning health care systems : gathering and using genomic information to improve patient care and research : workshop summary - Beachy, Sarah H.; Olson, Steve, 1956-; Berger, Adam C. (National Academies Press, 2015)
"The inclusion of genomic data in a knowledge-generating health care system infrastructure is one promising way to harness the full potential of that information to provide better patient care. In such a system, clinical practice and research influence each other with the goal of improving the efficiency and effectiveness of disease prevention, diagnosis, and treatment. To examine pragmatic approaches to incorporating genomics in learning health care systems, the Institute of Medicine Roundtable on Translating Genomic-Based Research for Health hosted a workshop which convened a variety of stakeholder groups, including commercial developers, health information technology professionals, clinical providers, academic researchers, patient groups, and government and health system representatives, to present their perspectives and participate in discussions on maximizing the value that can be obtained from genomic information. The workshop examined how a variety of systems are capturing and making use of genomic data to generate knowledge for advancing health care in the 21st century. It also sought to evaluate the challenges, opportunities, and best practices for capturing or using genomic information in knowledge-generating health care systems. Genomics-Enabled Learning Health Care Systems summarizes the presentations and discussion of the workshop"--Publisher's description